Pertanggungjawaban Pidana Korporasi terhadap Hak Cipta - Mahyani, Ahmad (DiH: Jurnal Ilmu Hukum, 2014)
Abstract. Not categorize a corporation as the subject of criminal law in the Copyright Act, the resulting corporation can not be prosecuted criminally liable. Corporations that commit crimes against copyright as if permission is granted impunity, namely freedom from punishment for his crimes in the form of piracy, reproduce and sell copyrighted works person. Though losses caused by corporate copyright offenders is enormous consequences for the country and for the owner or copyright holder than if the perpetrator is an individual. Accountability is delegated to the board of the corporation, be it director, manager, head of department, the operator, even though the employee has been going down during this proved unsuccessful raises deterrent effect. This research shows that in the case of copyright violations, the corporation must do the following may be prosecuted criminally managers with the maximum penalty for these crimes do not happen again in the future, along with the appropriate theory to apply. Also exposed to more forward thinking aspects of primum remedium if a violation has reached a disturbing level and cause ganggungan widely. It is recommended to take over the corporation who commits an offense if the implementation aspects of copyright primum remedium corporation went bankrupt, so that employees do not lose their jobs.Key words: Corporate, Subjects of Criminal Law, Copyright.